Ethics, Politics and Imperfection1 - Haldane, John (New blackfriars, 2008)
Recent social change has produced a relocation of the sense of personal identity from communities rooted in time and place to voluntary associations gathered around common interests. In consequence, the focus of moral consciousness has shifted from natural human values to constructed, systems of rights and obligations. Against these trends I argue that while times and circumstances change, the principal moral truths remain constant as do their implications for the place of ethics in public life: first, do no evil; and second, do unto others as you would have them do unto you. What lies beyond is not in the field of moral law, though it may be in the field of moral virtue. Here what is required is, as St Augustine, Adam Smith and Aurel Kolnai would say, human wisdom; and it part of human wisdom to recognize that in public life where what is at issue includes the well-being of the community, one does better to strive for the good and the acceptable than to seek for the perfect.